(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
The objective of this study is to find suitable weight quantity of organic material and retention time of acid mine drainage (AMD) treatment in column experiment. Hopefully the study will assist the miners to reduce the maintenance and operating cost after the treatment. The study using experimental column was carried out in the laboratory to investigate the effectiveness of organic material in treating acid mine drainage. Four different organic material weights were used; 50 g, 100 g, 200 g and 300 g. Five different retention times for each weights were used; 15 minutes, 30 minutes, 45 minutes, 60 minutes and 75 minutes. Analysis results showed that pH value of water sample had increased between 3.2 and 7.2 after the treatment. The lowest sulphate and sulphur contents after treatment were 967 mg/L at retention time of 75 minutes and 607 mg/L at retention time of 15 minutes respectively. Both experiments used 50 g organic material.